2017
DOI: 10.1111/acem.13257
|View full text |Cite
|
Sign up to set email alerts
|

A Simulation‐based Approach to Measuring Team Situational Awareness in Emergency Medicine: A Multicenter, Observational Study

Abstract: Team situational awareness supports adaptive teams and is critical for high reliability organizations such as healthcare systems. Simulation can provide a platform for research aimed at understanding and measuring TSA. This study provides a feasible method for simulation-based assessment of TSA in interdisciplinary teams that addresses prior measure limitations and is appropriate for use in highly dynamic, uncertain situations commonly encountered in emergency department systems. Future research is needed to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 41 publications
0
33
1
Order By: Relevance
“…In contrast to our results, similar pediatric simulations have shown no relationship between SA as assessed by the SAGAT method and achievement of the goal of the scenario [24]. In another study, this skill correlated with the team's clinical performance but did not correlate with the team's perception of shared understanding, team leader effectiveness, or team experience-similar to our results [25]. There are tools to improve SA.…”
Section: Discussioncontrasting
confidence: 63%
“…In contrast to our results, similar pediatric simulations have shown no relationship between SA as assessed by the SAGAT method and achievement of the goal of the scenario [24]. In another study, this skill correlated with the team's clinical performance but did not correlate with the team's perception of shared understanding, team leader effectiveness, or team experience-similar to our results [25]. There are tools to improve SA.…”
Section: Discussioncontrasting
confidence: 63%
“…In addition, team leaders were unable to confirm whether they had adhered fully to the protocol and often requested confirmation from others, which was frequently falsely positive. This loss of situational awareness is well documented [31,32,33,34), particularly when immersed in complex or perceived stressful clinical situations [35,36] as individuals focus on the minutiae rather than the overall event. This lack of insight whilst concerning, is in keeping with previous published studies that have found, those that underperform overestimate their performance and high performers underestimate theirs [37] illustrating that self-reporting is neither a suitable means of measuring the quality of resuscitation performance nor should it be relied upon when recording medical interventions in patient records.…”
Section: Discussionmentioning
confidence: 99%
“…For each participant and scenario, a composite SART score was computed using the following formula: SART Z U e (D e S ), where U summed the understanding representing familiarity and quality/quantity of the information being processed, D summed the attentional demand representing instability, variability, and complexity of the situation, and S summed the attentional supply representing perceived readiness for the activity, spare mental capacity, good concentration, and proper division of attention. The SA global assessment technique (SAGAT), 12 validated in many domains including health care, [13][14][15] was used to objectively quantify participants' SA. During each simulated scenario, participants were asked a number of SArelated questions, with at least 2 questions related to each of the displays (eg, Who are we treating?…”
Section: Quantification Of Situation Awarenessmentioning
confidence: 99%